Impossible interview with William Thomson - Lord Kelvin - Bagnoli, Franco (Il Colle di Galileo, 2020)
An impossible interview with a famous physicist, William Thompson Lord Kelvin, is presented, highlighting both his scientific contributions and his short temper.